2014
DOI: 10.1152/ajpgi.00018.2014
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of membrane metalloendopeptidase inhibits substance P stimulation of cholangiocarcinoma growth

Abstract: Substance P (SP) promotes cholangiocyte growth during cholestasis by activating its receptor, NK1R. SP is a proteolytic product of tachykinin (Tac1) and is deactivated by membrane metalloendopeptidase (MME). This study aimed to evaluate the functional role of SP in the regulation of cholangiocarcinoma (CCA) growth. NK1R, Tac1, and MME expression and SP secretion were assessed in human CCA cells and nonmalignant cholangiocytes. The proliferative effects of SP (in the absence/presence of the NK1R inhibitor, L-73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…In cholestatic liver injury, elevated serum levels of SP are observed in patients with chronic liver disease as well as in cholestatic rat models compared to respective controls suggesting an association between SP production and cholestatic liver damage [60]. Elevated SP secretion is also identified in cholangiocarcinoma (CCA) cell lines and administration of NK-1R antagonist L-733, 060 inhibits proliferation of CCA cells [61]. A study has demonstrated that BDL mice show elevated NK-1R expression in large cholangiocytes, and NK-1R −/− mice show attenuated large cholangiocyte proliferation and bile duct hyperplasia [62].…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
“…In cholestatic liver injury, elevated serum levels of SP are observed in patients with chronic liver disease as well as in cholestatic rat models compared to respective controls suggesting an association between SP production and cholestatic liver damage [60]. Elevated SP secretion is also identified in cholangiocarcinoma (CCA) cell lines and administration of NK-1R antagonist L-733, 060 inhibits proliferation of CCA cells [61]. A study has demonstrated that BDL mice show elevated NK-1R expression in large cholangiocytes, and NK-1R −/− mice show attenuated large cholangiocyte proliferation and bile duct hyperplasia [62].…”
Section: Pathways Associated With Cholangiocyte Responses and Theimentioning
confidence: 99%
“…(5) Inhibition of SP secretion and NK-1R signaling decreases cholangiocarcinoma growth. (6) Knockout of NK-1R reduces cholangiocyte hyperplasia and expression of collagen type 1, alpha 1 (Col1a1) and asmooth muscle actin (a-SMA) in bile duct-ligated (BDL) mice. (7) There are in vivo studies showing that NK-1R antagonists not only suppress the secretion of proinflammatory cytokines in the liver but also protect liver cells from apoptosis.…”
mentioning
confidence: 99%
“…Human CCA lines, Mz-ChA-1, SG231, HuH-28, CCLP, and HuCCT1 cells, express higher levels of TAC1 and NK-1R compared to human normal cholangiocytes [82]. SP increased cell proliferation of these CCA cell lines, and administration of NK-1R antagonist, L-733,060, decreased Mz-ChA-1 cell proliferation in vitro as well as tumor size in Mz-ChA-1 xenograft nude mice in vivo [82]. Although NK-1R antagonists may be therapeutic in inhibiting CCA tumor growth, current studies are limited and expression levels of TAC1 and NK-1R in human CCA tumor tissues and correlation with metastases or survival rates are still undefined.…”
Section: Substance Pmentioning
confidence: 97%
“…Administration of SP caused elevated ductular reaction and liver fibrosis in C57BL/6 wild-type mice, and NK-1R -/mice had improved liver conditions after BDL compared to wild-type mice with decreased HSC activation and fibrogenesis, indicating the association between the SP/NK-1R axis and cholestatic liver injury [81]. Human CCA lines, Mz-ChA-1, SG231, HuH-28, CCLP, and HuCCT1 cells, express higher levels of TAC1 and NK-1R compared to human normal cholangiocytes [82]. SP increased cell proliferation of these CCA cell lines, and administration of NK-1R antagonist, L-733,060, decreased Mz-ChA-1 cell proliferation in vitro as well as tumor size in Mz-ChA-1 xenograft nude mice in vivo [82].…”
Section: Substance Pmentioning
confidence: 99%